Technological enclaves and industrial districts: An analysis of the regional distribution of innovative activity in Europe - Raffaele Paci; Stefano Usai (European Regional Science Association (ERSA), 1998)
This paper explores the spatial distribution of innovative and productive activity across 109 regions of the European Union, thanks to an original databank on regional patents statistics. The main results worth highlighting are as follows. The technological activity in the EU appears to be highly concentrated, although concentration tends to decline over the eighties. This results from the huge differences between southern and northern Europe. As expected, there is a positive association between the regional distribution of innovative activity and labour productivity. Further, contrary to previous evidence on the United States, our data show a significant link between the specialisation in innovation and in production both at the country and at the industry level. This suggests that localised knowledge spillovers and agglomeration economies foster a local economic system towards a specialisation in both production and technology. More surprisingly there appears a negative correlation between technological concentration and aggregate productivity, that is the European regions which enjoy a more homogeneous distribution of their technological capability across different industrial sectors appear to be also characterised by a higher productivity level. This outcome may suggest the presence of positive inter-industry externalities that favour those regions which succeed in covering a broader range of technological activities.
Keywords: 330